A low-carbon and economically efficient dispatch model for distribution networks based on carbon emission flow theory - ZHAO Shuqi; XU Jianjun; TENG Xinliang; LI Yifan; PENG Cheng; YAN Limei (Zhejiang dianli)
In the context of dual carbon goals， the structure of the new-type power systems is becoming increasingly complex. Coordinating sources， loads， and energy storage within the systems to achieve economically efficient and low-carbon operation of distribution networks is a key area of current research. To address this， a low-carbon and economically efficient dispatch model for distribution networks based on carbon emission flow theory is proposed. First， an economically efficient dispatch model for distribution networks is established using a second-order cone flow model. Next， carbon potentials at each node are calculated based on the dispatch results， and an iterative method is employed to resolve the issue of unknown initial carbon storage levels in energy storage devices during the carbon potential calculation. Subsequently， a low-carbon demand response model is constructed with the goals of minimizing carbon emissions and the amount of curtailed renewable energy. Finally， simulation experiments are conducted using the IEEE 33-bus distribution network as an example， and the computational efficiency of the model is analyzed based on the IEEE 123-bus network. Comparisons are made with three other models. Experimental results indicate that the proposed dispatch model effectively reduces carbon emissions while maintaining economic efficiency and shortening calculation time， demonstrating promising application potential.